Persistent High Burden of Advanced HIV Disease Among Patients Seeking Care in South Africa's National HIV Program: Data From a Nationwide Laboratory Cohort - Carmona, Sergio; Bor, Jacob; Nattey, Cornelius; Maughan-Brown, Brendan; Maskew, Mhairi; Fox, Matthew P; Glencross, Deborah K; Ford, Nathan; MacLeod, William B (Clinical infectious diseases, 2018)
The South African national HIV program has increased antiretroviral therapy (ART) coverage over the last decade, supported by policy changes allowing for earlier ART initiation. However, many patients still enter care with advanced (<200 cells/μL) and very advanced (<100 cells/μL) HIV disease. We assessed disease progression at entry to care using nationwide laboratory data. We constructed a national HIV cohort using laboratory records containing HIV RNA loads and CD4 counts from 2004 to 2016 to determine entry into care. We estimated numbers and proportions of adults with the first CD4 count <100 cells/ μL or 100-199 cells/μL. We calculated relative risks of presenting with advanced disease associated with male sex. 8.04 million first CD4 results were identified. From 2005 to 2011, the proportion of patients entering into care with CD4 count <200 cells/μL declined from 46.8% to 35.6%. From 2011 onward, the proportion of patients entering ART with advanced HIV disease has remained relatively unchanged. In 2016, we estimated that of 654 868 patients entering care, 32.9% had advanced HIV disease, and 16.8% had very advanced HIV disease. Men were almost twice as likely as women (23.1% vs 12.6% ) to enter care with very advanced HIV disease. The proportion of patients presenting with advanced HIV disease in South Africa remains consistently high despite ART scale-up, representing a large and avoidable burden of morbidity. Early HIV diagnosis, rapid linkage to ART and approaches to attract men into early ART initiation should be prioritized.